Chemokines modulate glycan binding and the immunoregulatory activity of galectins - Sanjurjo, Lucía; Schulkens, Iris A.; Touarin, Pauline; Heusschen, Roy; Aanhane, Ed; Castricum, Kitty C. M.; De Gruijl, Tanja D.; Nilsson, Ulf J.; Leffler, Hakon; Griffioen, Arjan W.; Elantak, Latifa; Koenen, Rory R.; et al. (Communications biology, 2021)
Galectins are versatile glycan-binding proteins involved in immunomodulation. Evidence suggests that galectins can control the immunoregulatory function of cytokines and chemokines through direct binding. Here, we report on an inverse mechanism in which chemokines control the immunomodulatory functions of galectins. We show the existence of several specific galectin-chemokine binding pairs, including galectin-1/CXCL4. NMR analyses show that CXCL4 binding induces changes in the galectin-1 carbohydrate binding site. Consequently, CXCL4 alters the glycan-binding affinity and specificity of galectin-1. Regarding immunomodulation, CXCL4 significantly increases the apoptotic activity of galectin-1 on activated CD8 + T cells, while no effect is observed in CD4 + T cells. The opposite is found for another galectin-chemokine pair, i.e., galectin-9/CCL5. This heterodimer significantly reduces the galectin-9 induced apoptosis of CD4 + T cells and not of CD8 + T cells. Collectively, the current study describes an immunomodulatory mechanism in which specific galectin-chemokine interactions control the glycan-binding activity and immunoregulatory function of galectins. Sanjurjo et al investigate the role of galectins in immunomodulation, reporting that chemokines can control galectin immunomodulatory function through a mechanism involving galectin-chemokine binding pairs. Specifically, the authors find that CXCL4 binding changes the galectin-1 carbohydrate binding site, altering the glycan-binding affinity and specificity of galectin-1, as well as increasing the apoptotic activity of galectin-1 on CD8 + T cells.